Piotr Piotrowski Awangarda w cieniu Jałty. Sztuka w Europie środkowo-wschodniej w latach 1945–89 (Avant-Garde in the Shadow of Yalta. Art in East-Central Europe, 1945–1989) 2005. - Bernatowicz, Piotr (Nordlit, 2007)
Mieczysław Porębski, a distinguished Polish art historian of the 20th century, once expressed the demand for Polish art history to be researched simultaneously with foreign studies - as parallel fields. "We entered the research field of the old masters' art as partners in, so to say, a ‘furnished household', whereas in the field of contemporary art we are co-explorers, exploring a ‘virgin land'", as Porębski put it. The book by professor Piotr Piotrowski Awangarda w cieniu Jałty. Sztuka w Europie środkowo-wschodniej w latach 1945-89 (The Avant-Garde in the Shadow of Yalta. The Art in East-Central Europe, 1945-1989) fully accomplishes this demanding postulate which nowadays seems to be rather rarely remembered by Polish art historians. The explored area, the East-Central European countries, which emerged, as a result of the Yalta Conference, between the iron curtain and the border of The Soviet Union (including former Yugoslavia) appears at least as an ‘old maiden' land, where scientific penetration still seems to be necessary.
Keywords: Piotr Piotrowzki; Awangarda w cieniu Jałty. Sztuka w Europie środkowo-wschodniej w latach 1945-89; The Avant-Garde in the Shadow of Yalta. The Art in East-Central Europe; 1945-1989; Avant-Garde